The Effect of Cardiac Surgery in Children with Trisomy 13 And Trisomy 18: A Systematic Review and Meta-Analysis: Pharmaceutical Science-Medicine and surgery - A. Alzahrani, Dr. Samer; A. Alghamdi, Dr. Mohannad; F. Bin Muammar, Mohammed; Mahmoud A Khan, Dr. Abdulhakeem; Khaled Tayeb, Dr. Raghda (International Journal of Life Science and Pharma Research, 2022)
Infants with trisomy 13 or trisomy 18 frequently suffer from cardiac anomalies. Our study aims to look at the impact of using cardiac surgery on mortality and functional outcome in patients with trisomy 13 and trisomy 18. A search for articles was done on PubMed, Scopus, Science Direct and CENTRAL databases; from inception until 30th October 2022. Quantitative analysis was done using Meta XL and Review Manager 5.4. A p=-value of 0.05 was adopted as the significance threshold. The database search yielded 1,127 articles but only 17 were included in this systematic review. This paper reports a total of 2,551 trisomy cases. 672 cases were T13, 1478 cases were T18 and 401 cases were undefined. The calculated Odds Ratio (OR) was 4.20 95%CI, 2.70 - 6.52], with a p-value < 0.00001. There was also the finding that cardiac surgery had a more positive impact on mortality and discharge outcomes for T18 patients than T13 patients. The difference, however was statistically insignificant. In conclusion, the use of cardiac surgery to manage T13 and T18 patients is plausible, but other factors like post-operative complications should be taken into account.